From rule takers to rule makers : harmonising voluntary sustainability standards through Annex 6 of the AfCFTA Ppotocol on trade in goods - De Gama, Rafia (University of Pretoria, 2025)
Mini Dissertation (LLM (Trade and Investment Law In Africa))--University of Pretoria 2025.